Infecção experimental em suínos por Leptospira interrogans sorogrupos icterohaemorrhagiae e pomona - Santos, Adriana da Silva (2014)
Swine leptospirosis is a worldwide anthropozoonosis caused by spirochetes of the species Leptospira interrogans, predominantly by serovars Pomona, Icterohaemorrhagiae, Taravossi, Canicola Grippotyphosa and Bratislava. Experimental infection were performed in 18 sows at 40 days of age with L. interrogans serogroup Icterohaemorrhagiae serovar Conpenhageni strain Fiocruz L1-130, and serogroup Pomona serovar Kennewicki strain Pomona From divided in groups: GI (control), GII (inoculated with serogroup Pomona) and GIII (inoculated with serogroup Icterohaemorrhagiae). Clinical course of the disease, results of serological tests and detection of bacteria by polymerase chain reaction (PCR) and bacterial isolation during the experiment, were compared between groups. Additionally, the main histological changes observed in brain, liver, lymph nodes, lung and kidney of 12 animals experimentally infected and seropositive for leptospirosis were described. In lesions suggestive of the disease the technique of silver impregnation of Warthin-Starry, was used as direct detection method. During the experimental period, all samples of the GI (control) were negative in the microscopic agglutination test, with the GII positivity exclusive to serogroup Pomona in six animals from 6 dpi, and in GIII, only to serogroup Icterohaemorrhagiae in five animals from 3 dpi. At necropsy the only change was pale kidney in 50% of GI, 83.33% of GII and 83.33% of GIII (p> 0.05). Only in seropositive pigs was found lesions suggestive of leptospirosis as focal microgliosis in the brain (8.33%), lymphoid hyperplasia in lymph nodes of the mediastinum a nd mesentery (41.66%), mononuclear interstitial pneumonia (58.33 %), multifocal mononuclear hepatitis, further acute tubular nephrosis (100%) and interstitial nephritis (91.66%). There was a strong association between serological condition and lesions of mononuclear hepatitis (p = 0.0128), mononuclear interstitial nephritis (p = 0.0004), tubular nephrosis (p <0.0001) and mononuclear interstitial pneumonia (p = 0, 0377).